Association of sleep-wake pattern with cognitive performance and academic achievement in young adults - Altaf, Shafaq; Aftab, Anam; Fayyaz Khan, Komal; Anwar, Farah; Imran, Abeeha; Syed, Maira (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the association of sleep wake pattern with cognitive performance and academic achievement in young adults. Methods: It was a cross sectional study conducted in March 2019 after approval from the Institutional Review Board & Ethics Committee of the study setting on February 28, 2019. Total sample of the study was 189 calculated by using Rao software. Inclusion criteria was healthy young adults of age 18 to 24 years from Doctor of Physical Therapy department of Shifa Tameer-e-Millat University, Dar-ul-Shifa campus, Islamabad. Exclusion criteria included all those students who were married, diagnosed psychological disorder and were taking any sedatives. Data was collected through three questionnaires named Pittsburgh Sleep Quality Index (PSQI), Morningness-Eveningness Questionnaire (MEQ) and Montreal Cognitive Assessment (MOCA) in addition to inquiry regarding GPA of latest exam. Results: A total sample was 236 students with a mean age of 20.94±1.58 years with range 18-24 years. The sample comprised of males n=24 (10.2%) and females n=212(89.8%). Mean GPA was 3.10±0.53. MOCA showed that 70(29.66%) students had mild cognitive impairment, 166(70.34%) were students with normal cognition. The results obtained by applying independent T-test showed a significant difference of cognition between high and low achievers (P value: 0.029<0.05. Students who scored high were definite morning types. Conclusion: There is a significant association between cognitive performance and academic achievement with high achievers being definite morning types. Keywords: Cognition, Sleep, Academic success, Young adult.